Pengaruh Perilaku Guru Pendidikan Agama Kristen Terhadap Karakter Siswa Kelas VIII di SMP Negeri 1 Sitiotio Tahun Pembelajaran 2023/2024 - Ayu Iyan Maike Bakara; Limmarten Simatupang; Grecetinovitria M. Butarbutar (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to determine the positive and significant influence of PAK Teacher behavior on the character of students at SMP Negeri 1 Sitiotio for the 2023/2024 Academic Year. The method used in this research is a quantitative method with inferential statistical data analysis. The population was all 121 students in class VIII for the 2023/2024 academic year at SMP Negeri 1 Sitiotio and a sample of 36 people was determined, namely 30% of the total population using the Proportional Random Sampling technique. Data was collected using 40 positive closed items. The results of data analysis show that there is a positive and significant influence on the behavior of Religious Education Teachers on the character of students at SMP Negeri 1 Sitiotio for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) test the positive influence obtained by the value rxy = 0.594 > rtable(= 0.05,n=36) = 0.329, thus it is known that there is a positive influence between variable =34)= 2.042, thus there is a significant relationship between variable X and variable Y. c) Regression coefficient of determination test (r2) = 35.3%. 2) Influence test: Regression equation test, obtained the regression equation Y ̂="39.26"+0.97X. Thus Ha is accepted and H0 is rejected.